SOLUTION-FOCUSED BRIEF THERAPY (SFBT) DALAM KONSELING ANAK DAN REMAJA: TEKNIK, IMPLEMENTASI, DAN INTEGRASI NILAI-NILAI ISLAM - Nenny Litania; Amirah Diniaty (STKIP Subang, 2026)
ABSTRACT Psychological problems among children and adolescents—including anxiety, low self-esteem, interpersonal conflict, and risk behaviors—continue to rise, demanding effective and contextually sensitive counseling approaches. Solution-Focused Brief Therapy (SFBT) focuses on solutions rather than pathology, the future rather than the past, and client strengths rather than deficits. This conceptual article elaborates the theoretical foundations, core techniques, and implementation procedures of SFBT in child and adolescent counseling, integrating Islamic values relevant to the Indonesian context. Techniques examined include the Miracle Question, Exception-Finding Questions, Scaling Questions, Coping Questions, the EARS Technique, the Formula First Session Task (FFST), and the use of compliments. Each is mapped onto Islamic concepts such as husnudzon, tawakal, muhasabah, ikhtiar, sabar, and qana'ah, supported by relevant Qur'anic verses and hadiths. This integration rests on an epistemological alignment between SFBT's strength-based orientation and the Islamic view of human nature as inherently capable of positive change. Keywords: solution-focused brief therapy, Islamic integration, child and adolescent counseling ABSTRAK Permasalahan psikologis pada anak dan remaja—mulai dari kecemasan, rendah diri, konflik interpersonal, hingga perilaku berisiko—terus meningkat dan menuntut pendekatan konseling yang efektif, efisien, dan kontekstual. Solution-Focused Brief Therapy (SFBT) berfokus pada solusi, bukan patologi; pada masa depan, bukan masa lalu; dan pada kekuatan klien, bukan defisitnya. Artikel konseptual ini menguraikan landasan teoretis, teknik-teknik utama, dan prosedur implementasi SFBT dalam konseling anak dan remaja, sekaligus mengintegrasikannya dengan nilai-nilai Islam yang relevan dengan konteks Indonesia. Teknik yang dibahas meliputi Miracle Question, Exception-Finding Questions, Scaling Questions, Coping Questions, EARS Technique, Formula First Session Task (FFST), dan teknik pemberian pujian. Setiap teknik dipetakan terhadap konsep keislaman seperti husnudzon, tawakal, muhasabah, ikhtiar, sabar, dan qana'ah, beserta rujukan ayat Al-Qur'an dan hadits. Integrasi ini bertumpu pada keselarasan epistemologis antara orientasi kekuatan SFBT dan pandangan Islam tentang fitrah manusia sebagai makhluk yang berpotensi untuk berubah dan berkembang. Kata kunci: solution-focused brief therapy, integrasi Islam, konseling anak dan remaja